O dom na mansão: um caminho para o desenvolvimento social - Morais, Wanderley Buriti de (2018)
The Third Sector has emerged as one of the new perspectives brought by globalization and social development, contributing in turn to the recognition of potentialities and solutions to problems, such as poverty, marginalization and the reduction of social inequalities. Social inequality in Brazil, caused mainly by the poor distribution of income resulting from the concentration of the means of production, has always been a recurring theme of studies and research, as well as the object of actions of organizations from the most diverse sectors. Given this scenario, the Mansão do Caminho is an institution of the Third Sector that has been outstanding for its work with civil society. In this sense, our objective with this research is to analyze the participation of the civil society under the effect of the gift and the volunteer in the Mansão do Caminho in order to promote the social development in the neighborhood Pau da Lima, in Salvador, state of Bahia. The other objectives would be to show the institution building process, the reasons that lead people to collaborate with the organization, the possible public policies in partnership with the government, the vision of the people involved in the work performed and the differences of the House of the Path in relation to other entities that have already worked. This is an exploratory and descriptive research whose purpose is to study the theories of gift and social development present in the Caminho Mansion, in order to investigate the participation of the various actors in the contribution to the change of the social status of the region. As a research method, we intend to use the qualitative approach, using a script of semi- structured interviews and documents provided by the institution as a means of obtaining data. Our study broadens the discussion about the perspectives of the actors about the understanding of development, their visions regarding volunteering and how a Third Sector instrument contributes to the promotion of social development.